DINAMIKA RADIKALISME DAN KONFLIK BERSENTIMEN KEAGAMAAN DI SURAKARTA - Zakiyuddin Baidhawy (Studia Philosophica et Theologica, 2010)
This paper tries to search for religious portrait that supports the process of radicalization which is potential in rising social fragmentation; and to study process and dynamics of conflicts, and ethnic, social-economic, political, and intra and inter-religious based radicalism. This study finds out that: Firstly, Surakarta has been known as burning city in political and SARA issues in Central Java and national level. Facts has shown that since 1910 this city witnessed mass riots and amok which are nuanced by ethnic, religious, and political issues. Indeed, some riots outspread their excess and influences to other cities around, such as May 1998 and October 1999 tragedies. Secondly, ideologically Surakarta is one of the well known cities as the breeding ground of radical Islamic groups, and Javanese traditional belief (Kejawen), and they who still firmly grasp their ancestor values influenced by both Kasunanan and Mangkunegeran kingdoms. Lastly, some religious based conflicts and violence and terrorism seem to be contemporary trend of radicalism in Solo.